PENGARUH MOTIVASI DAN KEMAMPUAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KUTAI TIMUR - Sitti Sulhan Azikin (Jurnal Paradigma (JP), 2017)
The good work achievement of employee might be created if the employee has a motivation and skill to conduct the job description. Beside those factors, environtment factor also able to influence work achievement in the organization. Motivation as a push factor for reaching the best result, a motivational system consist of a tactic and strategy designed to stimulate and support the effort and its impact to enhancement of work achievement.